Does dual trigger improve euploidy rate in normoresponder? A cross-sectional study - Sule Yildirim Kopuk; Zeynep Ece Utkan Korun; Aysen Yuceturk; Ozge Karaosmanoglu; Caglar Yazicioglu; Bulent Tiras; Yigit Cakiroglu (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: With the introduction of the dual triggering-gonadotropin-releasing hormone (GnRH) analog and recombinant human chorionic gonadotropin (hCG) combination, women with a history of low mature oocyte proportion and empty follicle syndrome were shown to benefit from the dual trigger. Objective: To investigate whether dual triggering of oocyte maturation with a GnRH agonist (GnRHa) combined with hCG can affect the euploidy rate and improve in vitro fertilization outcomes for normoresponder women. Materials and Methods: In this cross-sectional study, 494 women who underwent controlled ovarian stimulation with hCG (n = 274) or dual triggering (hCG+GnRHa, n = 220) at Acibadem Maslak hospital, Assisted Reproductive Unit, from January 2019-2022 were enrolled in this study. Preimplantation genetic testing for aneuploidy was performed on all participants. Results: Both groups had similar baseline and clinical characteristics. Of the 881 embryos biopsied, 312 (35.4%) were reported as euploid in the hCG trigger group; in the dual trigger group, 186 (29.8%) of 623 screening embryos were reported as euploid. The hCG group had a higher euploidy rate per biopsied embryo, although the difference was not statistically significant (31.4 ± 26.5 vs. 26.5 ± 33.3, p > 0.05). Conclusion: In normoresponders, adding GnRHa for final follicular maturation to hCG did not improve the euploidy rate.